Hydrate phase equilibrium of ternary gas mixtures containing carbon dioxide, hydrogen and propane - Babu, Ponnivalavan; Yang, Ting; Veluswamy, Hari Prakash; Kumar, Rajnish; Linga, Praveen (Journal of Chemical Thermodynamics, 2013)
Hydrate phase equilibrium of the ternary guest mixtures containing carbon dioxide, hydrogen and propane at two different compositions were determined. Addition of mole composition of 2.5% propane to the fuel gas (CO2 (40%)/H-2 (60%)) mixture reduces the hydrate formation conditions by 66% at the temperature of 278.4 K. A Clausius-Clapeyron plot for the experimental results was plotted and from the slope, the enthalpy of hydrate dissociation was calculated. The enthalpy of dissociation of the mixed hydrate formed from a ternary gas mixture containing mole composition 38.1% CO2, 59.4% H-2 and 2.5% C3H8 was found to be 110 kJ.mol(-1) and hence it was concluded that the mixed hydrate formed structure II (sII) hydrates. Whereas for the ternary gas mixture containing mole composition 80.0% CO2, 18.8% H-2, and 1.2% C3H8, the enthalpy of dissociation of the mixed hydrate was found to be 78 kJ.mol(-1) and hence we believe the mixed hydrate formed structure I (sI) hydrate. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Gas hydrates; Global warming; Phase equilibrium; Pre-combustion; Thermodynamics

Hydrogen storage in clathrate hydrates: Current state of the art and future directions - Veluswamy, Hari Prakash; Kumar, Rajnish; Linga, Praveen (Applied Energy, 2014)
Hydrogen is looked upon as the next generation clean energy carrier, search for an efficient material and method for storing hydrogen has been pursued relentlessly. Improving hydrogen storage capacity to meet DOE targets has been challenging and research efforts are continuously put forth to achieve the set targets and to make hydrogen storage a commercially realizable process. This review comprehensively summarizes the state of the art experimental work conducted on the storage of hydrogen as hydrogen clathrates both at the molecular level and macroscopic level. It identifies future directions and challenges for this exciting area of research. Hydrogen storage capacities of different clathrate structures - sI, sII, sH, sVI and semi clathrates have been compiled and presented. In addition, promising new approaches for increasing hydrogen storage capacity have been described. Future directions for achieving increased hydrogen storage and process scale up have been outlined. Despite few limitations in storing hydrogen in the form of clathrates, this domain receives prominent attention due to more environmental-friendly method of synthesis, easy recovery of molecular hydrogen with minimum energy requirement, and improved safety of the process. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Clathrates; Gas hydrates; Hydrogen hydrates; Hydrogen storage; Promoters; Storage capacity

Enhanced clathrate hydrate formation kinetics at near ambient temperatures and moderate pressures: Application to natural gas storage - Veluswamy, Hari Prakash; Kumar, Sharad; Kumar, Rajnish; Rangsunvigit, Pramoch; Linga, Praveen (Fuel, 2016)
SNG (solidified natural gas) technology via clathrate hydrates is a potential method for large scale stationary storage of natural gas. Clathrate hydrate formation kinetics in presence of methane and 5.6 mol% tetrahydrofuran (THF) was investigated in an unstirred reactor configuration at moderate pressure and temperature conditions. It is well known that the presence of THF generally improves the thermodynamic stability of the resulting hydrate. In order to study the scale-up potential of this approach, kinetics of hydrate growth at temperatures close to ambient conditions and moderate pressures is required. Hydrate formation experiments were performed at three different temperatures - 283.2 K, 288.2 K and 293.2 K and at experimental pressures of 7.2 MPa, 5.0 and 3.0 MPa. Further, we report a synergistic effect of kinetic promotion of mixed methane hydrate formation by coupling THF and sodium dodecyl sulfate (SDS) at 293.2 K. For the first time, we observe rapid mixed methane/THF hydrate formation kinetics at 293.2 K in presence of just 100 ppm sodium dodecyl sulfate surfactant with methane gas uptake of 3.45 (+/- 0.17) kmol/m(3) of water in 1 h. This is also the first study to demonstrate such rapid hydrate formation kinetics with significant methane storage capacity at temperature of 293.2 K (closer to the ambient temperature). Further, substantial methane gas uptake of 3.52 (+/- 0.13) kmol/m(3) of water is possible even at reduced experimental pressure of 3.0 MPa and 283.2 K in 2 h. Minimal energy requirement in an unstirred reactor for mixed methane/THF hydrate formation storage can propel the SNG technology for large scale commercial deployment. Further improvement in the process can be achieved by optimizing the cooling requirement through innovative reactor design and operating the process in a semi-batch or continuous mode. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Methane hydrates; Natural gas storage; Rapid kinetics; surfactant; Tetrahydrofuran; Unstirred reactor

Rapid methane hydrate formation to develop a cost effective large scale energy storage system - Veluswamy, Hari Prakash; Wong, Alison Jia Hui; Babu, Ponnivalavan; Kumar, Rajnish; Kulprathipanja, Santi; Rangsunvigit, Pramoch; Linga, Praveen (Chemical Engineering Journal, 2016)
Natural gas (NG) is the cleanest burning fossil fuel and its usage can significantly reduce CO2 emissions from power plants. With its widespread use, there is an ever increasing need to develop technologies to store NG on a large scale. NG storage via clathrate hydrates is the best option for a large scale storage system because of its non-explosive nature, mild storage conditions, high volumetric capacity and being an environmentally benign process. In this work, we demonstrate a new method to achieve rapid methane hydrate formation in an unstirred tank reactor configuration (UTR) at moderate temperature and pressure conditions employing tetrahydrofuran (THF) as a promoter. For the first time, THF is reported to act both as a thermodynamic and an excellent kinetic promoter for methane hydrate formation. We demonstrate a multi-scale experimental validation of our method to a volumetric sample scale-up factor of 120 and internal reactor diameter scale-up factor of 10. Further, new insights on the dissociation behavior of the hydrates are reported. There is a competitive edge for storing NG via clathrate hydrates compared to compressed natural gas storage both in terms of cost and safety. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Energy storage; Enhanced kinetics; Gas hydrates; Natural gas storage; Tetrahydrofuran; Unstirred tank reactor